2019
DOI: 10.1007/s00277-019-03642-w
|View full text |Cite
|
Sign up to set email alerts
|

A novel flow cytometric method for enhancing acute promyelocytic leukemia screening by multidimensional dot-plots

Abstract: Acute promyelocytic leukemia (APL) is generally characterized by t(15;17)(q24;q21). In some cases, the classic translocation cannot be identified by conventional methods, since the PML-RARA fusion protein results from complex, variant, or cryptic translocation. The diagnostic algorithm of APL starts with screening methods, such as flow cytometry (FC), followed by fluorescence in situ hybridization or polymerase chain reaction to confirm the diagnosis. Our aim was to develop a novel proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
1
12
0
1
Order By: Relevance
“…However, results of the multidimensional flow cytometric analysis suggested unequivocally that both patients had APL. More than 95% of the pathological cells were detected in the APL gate pre-defined in our previous study in all multidimensional dot-plots in both cases (Figure 4) [17]. This means that the positions of pathological cells were typical for APL.…”
Section: Flow Cytometrysupporting
confidence: 54%
See 1 more Smart Citation
“…However, results of the multidimensional flow cytometric analysis suggested unequivocally that both patients had APL. More than 95% of the pathological cells were detected in the APL gate pre-defined in our previous study in all multidimensional dot-plots in both cases (Figure 4) [17]. This means that the positions of pathological cells were typical for APL.…”
Section: Flow Cytometrysupporting
confidence: 54%
“…One dot-plot was developed for each of the four tubes. During the analysis, the position of pathological cells was compared to the expected position of pathological promyelocytes in hypergranular and hypogranular APL, as defined in the previous study [17].…”
Section: Flow Cytometrymentioning
confidence: 99%
“…One previous study described a unique localization of APL on RPs applying a four‐tube 8‐color FCM panel including cytoplasmic myeloperoxidase. A limited number of APL ( n = 8) and NPM1+ AML samples were compared ( n = 12) (Karai et al, 2019 ). The authors defined a characteristic location of APL on created RPs using merged files for hypergranular ( n = 6) and hypogranular ( n = 2) APLs.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotype of the involved cells, often characterized by the expression of surface CD markers, is another feature playing an essential role in the diagnosis and prognosis of hematological malignancies and solid tumors. 3 , 71 , 72 Although flow cytometry is a practical technique to analyze the expression levels of CD markers, genetic alterations (including SNPs) affecting expression patterns of CD markers may cause significant limitations in the classification and precise prognosis of hematological malignancies. 73-75 As an example, CD38 rs6449182 is a known polymorphism in CLL and it has been shown that patients carrying the GG genotype of this polymorphism have more aggressive disease.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…Therefore, the evaluation of CD markers’ expressions is used as the first diagnostic strategy that is followed by an appropriate approach to monitoring the clinical course of leukemia. 3 Despite the fact that specific immunophenotypic patterns have been defined for the diagnosis of leukemia and lymphoma, results of studies in recent years indicate the heterogeneous expressions of CD markers in these malignancies. Numerous environmental and genetic factors like single nucleotide polymorphisms (SNPs) can alter the expression patterns of these surface markers.…”
Section: Introductionmentioning
confidence: 99%